An operational dispersion model for predicting pollution from a road. (4th August 2014) - Harkonen, J.; Valkonen, E.; Kukkonen, J.; Rantakrans, E.; Jalkanen, L.; Lahtinen, K.
We present here a mathematical model for predicting dispersion of pollution from a road, for use in a regulatory context. The model includes an emission model, treatment of the meteorological time series, a dispersion model, statistical analysis of the computed time series of concentrations and a graphical Windows–based user interface. The dispersion model is based on a partly analytic solution of the Gaussian diffusion equation for a finite line source. It allows for any wind direction with respect to the road. Dispersion parameters are evaluated using stability data produced by a meteorological preprocessing model, based on a Monin–Obukhov–type boundary layer scaling. The chemical transformation is modelled by using the discrete parcel method. It contains the basic reactions of nitrogen oxides, oxygen and ozone. The validity of the presented analytic solution has been tested against a more detailed numerical model; the results show that it can be used with confidence.